Reframing metaphor in translation: A cultural-linguistic analysis of Bumi Manusia and Garten der Menschheit with pedagogical insights - Merry Lapasau; Ryan Hidayat; Erna Megawati; Puji Anto; Vina Nur Indah Sari; Herlina Herlina (LITERA, 2026)
This article examines the conceptual metaphors employed in the Indonesian novel Bumi Manusia and its German translation, Garten der Menschheit, with a focus on how metaphorical expressions embody cultural cognition and how translation strategies reshape these metaphors across languages. Sixty-four conceptual metaphor was analysed in terms of their cognitive structure, type, cultural grounding, and translation technique. Drawing on Conceptual Metaphor Theory (CMT) and a comparative cultural-linguistic perspective, the study identifies dominant metaphorical domains including emotion, human character, nature and landscape, modernity, social hierarchy, physical movement, and embodiment. The analysis demonstrates how metaphors are adapted to align with the linguistic and cultural context of German-speaking readers, ensuring that the translated text preserves the depth and nuance of the original. The findings provide a qualitative mapping of metaphorical conceptualizations in both languages and offer insights into the cognitive and cultural processes involved in metaphor translation. In addition, the study outlines pedagogical implications for literary studies, intercultural competence, and metaphor awareness in multilingual classrooms.